Multimedia for Teaching Skills Development in Pre-service Teachers - Pusparini, Fitria; Setyorini, Daniar; Dewahrani, Yulilina Retno; Safitri, Dini (Bioedunis Journal, 2024)
A teacher must have teaching skills in order to become a professional teacher. The purpose of this article is to present the results of research on the development of teaching skills multimedia for microteaching courses in the Biology Education Study Program, FMIPA, State University of Jakarta. Multimedia is designed by combining text, images, audio and video to present basic teaching skills material in an interactive and interesting way. This research consisted of two years, in the first year four basic multimedia teaching skills were developed, namely: opening and closing lesson skills, class management skills and basic questioning skills and advanced questioning skills. This research is research and development (RnD) which was adapted into 7 stages from 10 steps of development research by Gall, Gall and Borg, including 1) research and data collection, 2) planning, 3) making prototypes, 4) testing first prototype, 5) prototype improvements, 6) field trials, 7) product improvements. The multimedia products developed are evaluated and assessed by experts, then revised based on the suggestions given and the results of field trials. The results of the research show that the multimedia developed is valid, practical and effective for improving teaching skills of pre-service teachers. Through this article the author wants to suggest that PKM or microteaching lecturers can use multimedia to practice basic teaching skills.